Transition to adult care in young people with neuromuscular disease on non-invasive ventilation - Alessandro Onofri; Hui-Leng Tan; Claudio Cherchi; Martino Pavone; Elisabetta Verrillo; Nicola Ullmann; Maria Beatrice Chiarini Testa; Renato Cutrera (BMC, 2019)
Abstract Background Long-term mechanical ventilation (LTV) with non-invasive ventilation (NIV) prolongs survival in patients with Neuromuscular Diseases (NMDs). Transition from paediatric to adult healthcare system is an undervalued and challenging issue for children with chronic conditions on mechanical ventilation. Methods this retrospective study aims to compare issues of young adults in age to transition to adult care (≥ 15 years old) affected by NMDs on NIV in two different Paediatric Respiratory Units in two different countries: Bambino Gesù Children's Hospital, Research Institute, (Rome, Italy) (BGCH) and the Paediatric Respiratory Unit of the Royal Brompton Hospital (London, UK) (RBHT). Results The median (min-max) age at starting ventilation was significantly different in the two groups (16 years old vs 12, p = 0.0006). We found significant difference in terms of median age at the time of observation (18 (15-22) vs 17 (15-19) years, p = 0.0294) and of type of referral (all the patients from the BGCH group were referred to paediatric services (n = 15, 100%), median age 18 (15-22); only 6 patients, in the RBHT group, with a median age 15.50 (15-17) years, were entirely referred to paediatric service). We found different sleep-disordered breathing assessments 6 full Polysomnographies, 7 Cardio-Respiratory Polygraphies and 2 oximetry with capnography (SpO2-tcCO2) studies in the BCGH group, while all patients of RBHT group were assessed with an SpO2-tcCO2 study. All patients from both groups underwent multidisciplinary assessment. Conclusions In conclusion, patients with NMDs on NIV in age to transition to adult require complex multidisciplinary management: significant efforts are needed to achieve the proper transition to adult care.